School-based evaluation an international perspective - Nevo, David, 1939- (Advances in program evaluation,, 2002)
Divided into two parts, this volume first discusses the concept of school-based evaluation, followed by a presentation of case studies of school evaluation from across the world. In part one, school-based evaluation is examined from three perspectives: school-based evaluation as a dialogue between internal and external evaluation; school evaluation from a perspective of institutional self-evaluation in a democracy and issues of definition, methods and implementation. The second part of the book presents case studies from Norway, England, The Netherlands, Austria, Spain, United States, Canada, Israel, Scotland and Germany. All of the case studies are based on actual experience with school-based evaluation in various educational and social contexts. Authors recognise the wide range of local constraints and reflect upon multiple evaluation perspectives, describing their educational context, evaluation perspective and specific school-based experience. They highlight difficulties encountered in their work, discuss the implications and make recommendations for further development of the concept of school-based evaluation and its practice. "School-Based Evaluation: An International Perspective" does not suggest internal/self school evaluation as an alternative to external "objective" evaluation. However, an attempt is made to advocate the combination of both for the benefit of school accountability and school improvement.